Managing and negotiating disagreements : a contemporary approach for conflict resolution - Bhardwaj, Bhawana; Sharma, Dipanker (Emerald Publishing Limited, 2024)
In today's diverse and multicultural work environments, conflicts have become inevitable. Managers in contemporary workplaces face significant challenges of dealing with conflict. They spend a considerable portion of their time, ranging from nine to fifteen weeks annually, on resolving disputes. The dynamic landscape of the modern workplace has given rise to novel and unusual challenges in maintaining harmony and handling disagreements effectively. This makes the skill of conflict management and negotiation a critical talent for success. Against the milieu of the Digital Era, authors Bhawana Bhardwaj and Dipanker Sharma delve into the multifaceted aspects of conflicts, encompassing their various manifestations and approaches to resolution, while exploring the implications of advanced technology and the integration of mixed workforces on the complexity of conflict resolution. In the era of digitalization, there has been a significant drift in the management practices where negotiations are now managed online and through several AI tools. The discourse on using contemporary tools like NSS (Negotiation Support System) will benefit and enable the readers to fine-tune with this changing paradigm. The authors also explore the transformative role of Artificial Intelligence (AI) in the conflict resolution domain. The Book delve into the proactive approaches to conflict resolution by reframing conflict as a normal and potentially beneficial phenomenon. Written with a diverse readership in mind, this monograph caters to students, educators, researchers, managers, and policymakers alike.